1998
DOI: 10.1007/s001170050465
|View full text |Cite
|
Sign up to set email alerts
|

Bedeutung der CT für die Beurteilung regionärer Lymphknotenmetastasen bei kolorektalen Karzinomen

Abstract: Evidence of regional nodal metastatic disease is only relevant for rectal cancer, colon polyps, and for locally excised tumors when considering present surgical concepts for the treatment of colorectal cancer. In these cases CT analysis using the broadened criteria for N1 proposes a valuable argument regarding possible preoperative radiotherapy or an operative revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
4
0
3
Order By: Relevance
“…Conventionally, a LAD of > 10 mm has been accepted as a potential sign of LN metastases [5, 6]. Reported sensitivities and specificities of LN size and/or clusters of ≥ 3 LNs were 56–84.3% and 58–95%, respectively [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, a LAD of > 10 mm has been accepted as a potential sign of LN metastases [5, 6]. Reported sensitivities and specificities of LN size and/or clusters of ≥ 3 LNs were 56–84.3% and 58–95%, respectively [59].…”
Section: Discussionmentioning
confidence: 99%
“…The LNs measuring > 10 mm in computed tomography (CT) images have conventionally been regarded as a sign of nodal involvement of cancer [5, 6]. Previous studies have reported the diagnostic accuracy of such CT measures, using axial images [59].…”
Section: Introductionmentioning
confidence: 99%
“…These factors are accepted as predictors of lymph node involvement in colorectal cancer (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Therefore, we should conduct further analyses with a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous findings, it was reported that lymph nodes with a diameter larger than 1 cm, three or more clustered lymph nodes regardless of their size, and irregular surface, were predictive factors for lymph node involvement (sensitivity: 66-96.3% and specificity: 35-81%) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). On the other hand, thus far, there has only been a single report stating the lymph node involvement of rectal NETs predicted by CT (19), and there have been no reports concerning colorectal NETs.…”
mentioning
confidence: 89%
“…zum präoperativen Staging eines kolorektalen Karzinoms eingesetzt werden[47]. In der CT kann zwar nicht zwischen T1-und T2-Stadium des Tumors unterschieden werden[48], dies ist allerdings für die Therapieentscheidung nicht wichtig[49]. In einem Vergleich mit Endosonographie, MRT und Endo-MRT (mit endoanaler Spule) schneidet die CT hinsichtlich Sensitivität und Spezifität in der Beurteilung des T-Stadiums eines Rektumkarzinoms schlechter ab[38].…”
unclassified